Analysis of Factors Affecting Poverty in North Sumatra - Waruwu, Putri; Sitorus, Annisa Mardiah; Lumban Tobing, Winda Sartika; Sianturi, Samuel (Outline Publisher, 2024)
Poverty is a limitation of economic conditions to meet the average standard of living of people in an area. This tariff condition is marked by the low ability of income to meet basic needs in the form of food, clothing, and shelter, because not all economic sectors can become the basis of the sector, resulting in low income distribution, and also because of the low quality of human life and income levels. response is still high. This study uses a research method with a quantitative approach. The data used in this study are secondary data and Time Series data for 2005 - 2022. The purpose of this study is to determine the effect of the Open Unemployment Rate, Human Development Index, and Gross Regional Domestic Product on the basis of salary prices, Index on the Number of Poor Population in the Province Sumatra. North. The analysis technique in this study uses Multiple Linear Regression Analysis. The results in this study indicate that the variable Open Unemployment Rate has a positive and significant effect on the Number of Poor People, the Human Development Index, and the Gross Regional Domestic Product on the Basis of Use, the Index has a negative and significant effect on the Number of Poor People